Analisis Modus Operandi Tindak Kejahatan Menggunakan Teknik Komunikasi Love Scam Sebagai Ancaman pada Keamanan Sistem Informasi - Ervan Yudi Widyarto; Dita Kusuma Hapsari (Ridwan Institute, 2022)
The development of information and communication technology that is increasingly widespread in today's world, has led to a new phenomenon called cybercrime, it can even be done instead of communication through love scams or scammer love. In this study, we would like to conclude several factors that can lead to crime using love scam communication techniques to provide a solution. The phenomenon of love scam or scammer love. This action is an act of fraud under the guise of romance. Usually the perpetrator uses tricks or instead of trust that involves the emotions or feelings of the victim and then takes advantage of those feelings or good intentions to commit fraud. indeed it can not be seen directly. That's what causes hackers to be interested in using the Internet as a medium of communication and at the same time forming a community, because the Internet is the fastest way for hackers to act and interact with victims without having to show their true identity.